2009
DOI: 10.3116/16091833/10/3/165/2009
|View full text |Cite
|
Sign up to set email alerts
|

Acoustooptic and acoustic properties of KLiB4O7 crystals

Abstract: The acoustic and acoustooptic (AO) properties of KLiB 4 O 7 crystals are experimentally studied and analysed. It is shown that the above crystals can be used as a material for AO applications. The AO figure of merit calculated for the slowest acoustic wave is equal to M 2 =(332±120)×10 -15 s 3 /kg. Propagation of the acoustic energy flow in KLiB 4 O 7 for the cases of transverse and longitudinal acoustic waves is considered. It is shown that the obliquity for the slowest transverse wave is relatively small and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…They are widely used in parametric optical oscillators as functional elements [13,14]. Recently we have shown that the borate crystals may also be used as acoustooptic materials, in particular for acoustooptic operation of laser radiation in the short-wavelength spectral range [15][16][17][18][19][20][21][22][23]. We should also notice that the acoustooptic interactions do not require a lack of centre of symmetry, being possible even in the isotropic glasses.…”
Section: Introductionmentioning
confidence: 99%
“…They are widely used in parametric optical oscillators as functional elements [13,14]. Recently we have shown that the borate crystals may also be used as acoustooptic materials, in particular for acoustooptic operation of laser radiation in the short-wavelength spectral range [15][16][17][18][19][20][21][22][23]. We should also notice that the acoustooptic interactions do not require a lack of centre of symmetry, being possible even in the isotropic glasses.…”
Section: Introductionmentioning
confidence: 99%